الجریمة الاقتصادیة - جریمة تبیض الأموال نموذج - مدلل, حفناوي (جامعة الوادي - University of Eloued, 2015)
Speaking of economic crime leads to crimes against the state economy and the risks or effects caused to these crimes brown and economic structures, multi- state, where the spread of these crimes are terrible at in recent years , particularly in the light of scientific development and technological progress, and in the light of globalization What made all nations to give the alarm and the fight against these crimes and to treat all means to protect their economies, maintaining its stability because the stability of the economy of the stability and progress of the country . From there , this study is to shed light on economic crime and the most important forms
economic crime Laundering of money crime - model
مقال
Keywords: Crime, Economics, economic crime, the economic system, the law, legislation, law Alaguetsada, elements of the crime, the penalty, the Algerian legislator.